2014
DOI: 10.1080/08998280.2014.11929039
|View full text |Cite
|
Sign up to set email alerts
|

Steroid-Resistant Nephrotic Syndrome Secondary to Primary Focal Segmental Glomerulosclerosis and Smoldering Multiple Myeloma

Abstract: We present a patient with steroid-resistant nephrotic syndrome due to focal segmental glomerulosclerosis along with smoldering multiple myeloma. While investigating the cause of proteinuria, a monoclonal gammopathy with a negative kidney biopsy for myeloma-related pathology was discovered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The results of our study are similar to those of previous reports. 7 The results indicate that LT3S is associated with the severity of the disease in NS patients, suggesting that LT3S may be a self-protective mechanism under the disease state. By reducing the concentration of thyroid hormone, protein catabolism is reduced, resulting in a decrease in the basal metabolic rate and reduced energy consumption.…”
Section: Discussionmentioning
confidence: 79%
“…The results of our study are similar to those of previous reports. 7 The results indicate that LT3S is associated with the severity of the disease in NS patients, suggesting that LT3S may be a self-protective mechanism under the disease state. By reducing the concentration of thyroid hormone, protein catabolism is reduced, resulting in a decrease in the basal metabolic rate and reduced energy consumption.…”
Section: Discussionmentioning
confidence: 79%
“…Of these studies, three suggested that there was little or no correlation between FSGS and plasma cell proliferative disorders. In a study by Shah et al ( 12 ), the NS of the patient was not resolved by hormone therapy, however, the patient's smoldering MM did improve. Paueksakon et al ( 1 ) identified that 13 out of 87 (14.9%) patients with MGUS and renal damage had FSGS-like lesions, and thus, the FSGS was not considered to be primary.…”
Section: Discussionmentioning
confidence: 89%
“…All of these factors support the notion that the two diseases are associated. While the patients in a study by Shah et al ( 12 ) exhibited a reduction in serum monoclonal protein and light chain protein levels following the use of hormones for 3 months, the proteinuria did not resolve. It is possible that the improvement in secondary FSGS required a longer time than that required to control the primary disease.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation